Energetics of best performances in elite kayakers and canoeists - Buglione, A.; Lazzer, S.; Colli, R.; Introini, E.; Di Prampero, P. E (Medicine & Science in Sports & Exercise, 2011)
Purpose: The objectives of this study were 1) to validate a new test to determine maximal oxygen uptake (VO2max) in kayakers, 2) to calculate the energy cost (Ck) of high-level kayakers and canoeists at submaximal and race speeds, and 3) to correlate individual best performances achieved in practice with those theoretically calculated. These were obtained from the individual relationships Er = f(t) and Emax = f(t), where Er is the metabolic power required to cover the distance in question and Emax is the maximal metabolic power. The time yielding Er = Emax was assumed to yield the best performance time.